The poem was represented in the poetry of Mohammad Al-mathloom: - The weighted poem as a model - - Bahid, Zain el Abidine Hussein Ali; Abbas Kadhim, Samir (Al-Adab Journal, 2020)
The rhythm in Mohammad's poetry represents an ever-lasting history extending horizontally in his poetic group from his first collection to the last one sometimes writing out separate texts for him and sometimes overlapping with other forms. Mohammad writes the rhythm poem in its two forms the classic vertical form and its source is the Arabic literary heritage and the free verse form and its source is pioneers poets, in this way the poem is pluralistic as cultural references in writing the rhythm poem The poet Mohammad benefited from all poetry rhythm pure and nonpure meter and he did not leave a technique in color except he benefited from it such as the technique of rotating, accelerating and embedding the converging meter had the largest share of all the meters used.